The influence of work discipline, work motivation, and career development on employee performance with organizational culture as an intervening variable at PT. Bank Rakyat Indonesia, Pekanbaru Lancang Kuning branch office - Evi Juli Miherni Purba; Syaifuddin Syaifuddin; Yeni Ariesa (Journal of Economics and Business Letters, 2023)
This research was conducted at PT. Bank Rakyat Indonesia, Pekanbaru Lancang Kuning Branch Office, with the aim of determining the influence of work discipline, work motivation, and career development on employee performance, with organizational culture as the intervening variable. The subjects of this research were the employees of PT. Bank Rakyat Indonesia, Pekanbaru Lancang Kuning Branch Office, totaling 123 samples. This study utilized questionnaires as a data collection tool. Tests employed to evaluate the research instruments included validity testing, reliability testing, and classic assumption testing. Data analysis involved multiple linear regression analyses, hypothesis testing using T-tests (partial) and F-tests (simultaneous), as well as the determination coefficient and the Sobel test. Based on the T-test and F-test, it was proven that the Work Discipline (X1), Work Motivation (X2), Career Development (X3), and Organizational Culture (Z) variables significantly and positively influence the Employee Performance (Y) variable simultaneously. The determination coefficient for model 1 was 53.7% and for model 2 was 86.6%. The results of this research indicate that work discipline, work motivation, and career development have a positive and significant influence on employee performance, with organizational culture acting as the intervening variable.